The Influence of Influencer Marketing and Brand Engagement on Purchase Intention - Hadi, Hanna Shafira; Kinanti, Prasasti Sekar; Khasanah, Imroatul; Soesanto, Harry (LifeSciFi, 2025)
In the digital era, companies are increasingly leveraging the internet to market their products and engage with consumers. One of the most commonly adopted strategies today is influencer marketing. This approach has gained popularity in tandem with the rapid development of digital technologies, as businesses strive to maintain meaningful connections with their customers. Influencer marketing capitalizes on the credibility and appeal of influencers to foster meaningful and sustained relationships between brands and consumers by leveraging the interactive and communicative features of social media platforms. This study aims to examine how influencers’ attractiveness, trustworthiness, and expertise influence consumers’ purchase intentions, with brand engagement serving as a mediating variable. The research population consists of Indonesian individuals who are aware of or have seen influencers promoting products and have made a purchase. A total of 110 respondents participated in the study. Data collected through questionnaires were analyzed using the AMOS 24.0 software. The findings reveal that influencers’ attractiveness, trustworthiness, and expertise positively impact brand image and purchase intention. Additionally, brand engagement significantly influences purchase intention.